Decayed gods : origin and development of Georges Dumézil's "idéologie tripartie" - Belier, Wouter W. (Studies in Greek and Roman Religion, 1991)
In 1930 Dumézil wrote an article in which he defended the Indo-European character of the Indian varnas . In 1986 he was completing his final 25 Esquisses , research proposals the aim of which was to allow his model of the 'idéologie tripartie' of Indo-European traditions to be applied to his 'disciples'. According to this model Indo-European traditions were typified by a threefold division into functions of society, the world of the gods, and the heroic traditions. These were the functions of sovereignty, power and 'fertility'. This theoretical model was elaborated by Dumézil in a large number of books and articles. Between 1930 and 1986 he broadened enormously the amount of data on which his model was based. To do so he had regularly to adapt and reformulate his model. This was not without consequences for the material which he had interpreted earlier on. In this study a detailed description is given of this process of reformulation and reinterpretation and the conclusion is that the totality of the various models does not, despite its aesthetic attraction, satisfy the criteria which should be set for scientific models.